Transformación económica argentina - Spinelli, Armando P. (1957)
We are facing the difficult task of the political and juridical reorganization in order to adjust it to the new economic criteria, the most important changes being connected with the competition. We are endeavouring to adjust it, soften it or eliminate it. To this effect two ways are open: planning or control with their different varieties in accordance with the causing impulses: social, political or essentially economic, with their various shades in the different countries, but all of them having the same general characteristics, but of rectifying or over throwing the liberal principles. The author refers particularly to the "agricultural readjustment Act" in the United States and the French law project of 1936 and emphasizes the advantages of the "concerted economy" (neocorporativism). For Argentina the most suitable way would be to create an organization which would authorize the functioning of voluntary agreements, establish the limits of their application and create control institutions in order to prevent abuses admitting at the same time the possibility of transforming the voluntary agreements in obligatory ones, if the State considers that its action should be amplified.